Intercepting IRE1 kinase‐FMRP signaling prevents atherosclerosis progression - Zehra Yildirim; Sabyasachi Baboo; Syed M Hamid; Asli E Dogan; Ozlem Tufanli; Sabrina Robichaud; Christina Emerton; Jolene K Diedrich; Hasan Vatandaslar; Fotis Nikolos; Yanghong Gu; Takao Iwawaki; et al. (EMBO Molecular Medicine)
Abstract Fragile X Mental Retardation protein (FMRP), widely known for its role in hereditary intellectual disability, is an RNA‐binding protein (RBP) that controls translation of select mRNAs. We discovered that endoplasmic reticulum (ER) stress induces phosphorylation of FMRP on a site that is known to enhance translation inhibition of FMRP‐bound mRNAs. We show ER stress‐induced activation of Inositol requiring enzyme‐1 (IRE1), an ER‐resident stress‐sensing kinase/endoribonuclease, leads to FMRP phosphorylation and to suppression of macrophage cholesterol efflux and apoptotic cell clearance (efferocytosis). Conversely, FMRP deficiency and pharmacological inhibition of IRE1 kinase activity enhances cholesterol efflux and efferocytosis, reducing atherosclerosis in mice. Our results provide mechanistic insights into how ER stress‐induced IRE1 kinase activity contributes to macrophage cholesterol homeostasis and suggests IRE1 inhibition as a promising new way to counteract atherosclerosis.